2012
DOI: 10.1371/journal.pone.0046102
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Combined Exposure of 900 MHz Radiofrequency Fields and Doxorubicin in HL-60 Cells

Abstract: Human promyelocytic leukemia HL-60 cells were pre-exposed to non-ionizing 900 MHz radiofrequency fields (RF) at 12 µW/cm2 power density for 1 hour/day for 3 days and then treated with a chemotherapeutic drug, doxorubicin (DOX, 0.125 mg/L). Several end-points related to toxicity, viz., viability, apoptosis, mitochondrial membrane potential (MMP), intracellular free calcium (Ca2+) and Ca2+-Mg2+ -ATPase activity were measured. The results obtained in un-exposed and sham-exposed control cells were compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 27 publications
(18 reference statements)
1
20
0
Order By: Relevance
“…I read with great interest an article by Jin et al "The Effect of Combined Exposure of 900 MHz Radiofrequency Fields and Doxorubicin in HL-60 Cells," published in the Sep 2012 issue of PLOS ONE Journal (Jin et al 2012). The authors of the article reported some interesting findings on the induction of adaptive response by pre-exposure of HL-60 Cells to radiofrequency (RF) radiations.…”
mentioning
confidence: 99%
“…I read with great interest an article by Jin et al "The Effect of Combined Exposure of 900 MHz Radiofrequency Fields and Doxorubicin in HL-60 Cells," published in the Sep 2012 issue of PLOS ONE Journal (Jin et al 2012). The authors of the article reported some interesting findings on the induction of adaptive response by pre-exposure of HL-60 Cells to radiofrequency (RF) radiations.…”
mentioning
confidence: 99%
“…The effects varied from greatly reproducible data with synergistic effect, additive effect, or biological effect [8].…”
Section: Discussionmentioning
confidence: 99%
“…This configuration seems to be appropriate to achieve high scale removal efficiency, where a magnetic field into the membrane process was employed as a strategy to prevent and eliminate scale formation on the membrane surface [13]. In other cases, the direction of propagation of the incident field was parallel to the plane of the membrane [14]. This configuration is mainly used when studying biological systems.…”
Section: A Conductive Membranes Used In Rf Propagationmentioning
confidence: 99%